A Multi-Resonant based reference feedforward adaptive voltage control for Grid-Forming inverter in island mode to compensate system uncertain and harmonic distortions - Renzhi Huang; Zaijun Wu; Xueyong Xu; Xiangjun Quan; Mingfei Li; Zichen Wang; Mengnan Liu (International Journal of Electrical Power & Energy Systems)
This paper investigates a novel adaptive voltage control over a three-phase grid-forming (GFM) inverter. The proposed voltage controller includes two function parts: power control input and signal control input. The former improves dynamic performance by taking advantage of state feedback, load current feedforward, and reference feedforward, while the latter, a time-variant signal in reference feedforward, considers uncertainties of system parameters and load disturbances. In order to compensate for harmonic distortion on loads, a multi-resonant control is added to the signal control input. Then, a multi-resonant based reference feedforward adaptive control strategy is put forward. Thanks to its linearization, the stability of the strategy is ensured by the mature linear control theory instead of the Lyapunov stability theory. Then, the principles of parameter selection based on the root locus method are introduced to improve the dynamic performance of this technique. Compared with classical PI/PR methods or other adaptive ones, this newly proposed adaptive control method synthesizes high robustness, excellent voltage regulation performance, and low total harmonic distortion under nonlinear loads in island mode. The experiments verify its effectiveness on a GFM inverter using a TI TMS320F28335 DSP.